A new Troglosiro species (Opiliones, Cyphophthalmi, Troglosironidae) from New Caledonia - Sharma, Prashant; Giribet, Gonzalo (Zootaxa, 2005)
A new species of Cyphophthalmi belonging to the New Caledonian endemic genus Troglosiro Juberthie, 1979 is described and illustrated using SEM, including the first description of a troglosironid ovipositor. T. longifossa sp. nov., known only from its type locality in Port Boisé, and found at low elevation near sea level, constitutes the seventh species of Troglosiro to be described to date. The new species has a unique disposition of the four ventral opisthosomal gland pores in the anterior portion of a long depression of the sternal segments 3 to 7. Information on other specimens recently collected in New Caledonia indicates that the number of described species in the island is a gross underestimate of the real diversity of New Caledonian Cyphophthalmi, both in number of species and morphology.